The role of narratives in the Brazilian environmental arenas - Silvino, Amanda Sousa; Viglio , José Eduardo; Calvimontes, Jorge; Resende de Moraes, Raíssa; Ferreira , Lúcia da Costa (Sustainability in Debate, 2025)
Environmental issues rank among the most pressing challenges of the 21st century. This article explores the complementarity between the theoretical and methodological approaches of Political Arenas and Narratives in addressing conflicts and decision-making processes related to environmental issues. To this end, we conducted an extensive literature review and a qualitative analysis of research produced within the Postgraduate Programs in Social Sciences and Environment and Society at the University of Campinas (Unicamp). Our objective was to operationalise both concepts and assess how these approaches contribute to structuring academic inquiry. The findings suggest that identifying the functions of narratives within political arenas helps to uncover the complexity and contradictions inherent in socio-environmental dynamics. We conclude that addressing environmental challenges requires acknowledging multiple perspectives and social tensions to foster transformative action. This study underscores the importance of interdisciplinary and qualitative methodologies for understanding the social dimensions of environmental issues.